Raging Heat [compact disc, unabridged] - Castle, Richard (Nikki Heat series, 2014)
An illegal immigrant falls from the sky and NYPD Homicide Detective Nikki Heat's investigation into his death quickly captures the imagination of her boyfriend, Pulitzer Prize-winning journalist Jameson Rook. When he decides to work the case with Heat as his next big story, Nikki is at first happy to have him ride along. But when Rook's inquiry concludes that Detective Heat has arrested the wrong man for the murder, everything changes.